Dynamic Strength and Muscle Power in Elite and Non-Elite Brazilian Jiu-Jitsu (Bjj) Athletes: A Systematic Review with Meta-Analysis - Aedo-Munoz, E; Brito, C (Federacion Espanola de Docentes de Educacion Fisica, 2024)
A systematic review with meta-analysis on the dynamic strength and muscle power in elite and non-elite Brazilian jiu-jitsu (BJJ) athletes is essential to provide a comprehensive and quantitative evaluation of the physical attributes critical for performance, allowing for a better understanding of the training needs and physical characteristics that distinguish different levels of athletes in this sport. Therefore, this study endeavors to comprehensively synthesize existing literature on muscle strength and power in the context of BJJ, making a comparative analysis between elite and non-elite athletes. The research was conducted up to April 20, 2022, employing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol to systematically search electronic databases using the keywords: "Brazilian Jiu-jitsu" or "BJJ" or "Jiu-jitsu" and "power" or "muscle power" or "physical fitness" or "muscle strength" or "strength." Following a rigorous selection process, 26 articles were included in the systematic review. Subsequently, the GRADE (Grading of Recommendations, Assessment, Development, and Evaluations) tool was employed for evidence assessment. The primary assessments of dynamic strength encompassed protocols involving the Bench press, squat, and pull-up-gi. In the context of muscle power, the meta-analysis considered parameters such as the countermovement jump (CMJ), standing long jump, and variables derived from jump power assessed on the force platform, including Peak velocity, peak power, mean power, and maximum force. The data showed a substantial effect size for strength [1.012 (p≤0.0001)] and a moderate effect size for power [0.619 (p≤0.0001)], indicating superior performance among elite athletes compared to their non-elite counterparts. Although power is predominant in most BJJ actions, strength emerges as a crucial element distinguishing elite from non-elite athletes in this sport. This realization carries significant implications for training and injury prevention, as both strength and power necessitate specialized training to enhance performance in the sport. © 2024 Federacion Espanola de Docentes de Educacion Fisica. All rights reserved.